The «Absolute Futility» isn't Absolute: Concerning the Necessity of Reconsideration of Existing Time-Based Criterion for Stopping Resuscitation Attempt - A. A. Birkun (Общая реаниматология, 2020)
Despite the progress in the modern resuscitation science, optimal duration of a cardiopulmonary resuscitation (CPR) attempt is not defined yet.It seems appropriate to initiate an open discussion within the Russian medical research community, concerning the development of uniform legislated criteria for stopping resuscitation, considering the best scientific evidence and current international guidelines, with subsequent introduction of harmonized amendments to the clinical practice guidelines for CPR.